K rešitvi usmerjen pristop kot podpora soustvarjanju želenih izidov v delovnem odnosu - Mešl, Nina (Socialno delo, 2018)
Solution-focused approach in social work, in which social workers take into account and respect the capabilities of their interlocutors to solve problems, and understand their role in creating the context for possible changes, has been developed at the Faculty of Social Work for two decades. Two generations of students of the Psychosocial Support and Help Module have tested the approach in the context of learning process on their practical placements. Skills of the approach were used in the context of the working relationship of co-creation with one or more interlocutors. A qualitative analysis of final assignments in which students presented the use of the approach and analysis of the work process showed that they perceive the approach as very supportive for social work. Most often students decided to use the element of exception-finding questions, scaling question, miracle question and relationship questions. When using the elements, they saw the greatest challenge in the persistent exploration of details and in the reframing of the problem-oriented speech to a speech that is directed toward solutions.
Keywords: delovni odnos; Fakulteta za socialno delo; kompetence; perspektiva moči; pogovor; psihosocialna podpora; socialno delo